ANALISIS KINERJA PRODUKSI AGROINDUSTRI KERUPUK KEMPLANG DI SENTRA PRODUKSI KEMPLANG SKIP RAHAYU KELURAHAN BUMI WARAS KECAMATAN BUMI WARAS BANDAR LAMPUNG - Dewi Hermania; Muhammad Irfan Affandi; Fembriarti Erry Prasmatiwi (Lampung University, 2022)
This research aims to analyze the performance production of baked fish crackers kerupuk kemplang in Skip Rahayu Agroindustry, Bumi Waras Subdistrict, Bandar Lampung. The method used in this research is a survey method. The location was determined purposively with the consideration that the area is the production center of kerupuk kemplang agroindustry in Bandar Lampung. The samples in this study are 13 baked fish crackers kerupuk kemplang agroindustry owners that are randomly selected disproportionately. Data collected were in March - April 2021 and the data analysis method used in this research was qualitative and quantitative descriptive analysis. The study results are kerupuk kemplang agroindustrial performance based on productivity aspect, capacity, quality, speed of delivery, and the speed of the process has been good, but based on the flexibility aspect it is not optimal. Key words: kerupuk kemplang, production performance